Perspectives on Teaching and Learning Chinese Literacy in China - Leung, Cynthia B.; Ruan, Jiening; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
This is one of two volumes by the same editors that explore historical, philosophical, and cultural perspectives on literacy in China. This volume focuses on Chinese literacy, while the other volume is on English literacy. Since the founding of the People$1 (Bs Republic of China, the country has witnessed a dramatic increase in its literacy rate, but not without challenges. The essays in this volume provide a comprehensive, cross-disciplinary look at changes in Chinese literacy education from ancient times to the modern day. Together, the essays address a wide array of topics, including early Chinese literacy development, children$1 (Bs literature, foreign translated literature, and uses of information technology to teach Chinese. This authoritative text brings clarity and precision to the field and serves as a vital core resource for those who want to expand their understanding of Chinese literacy education. Its scope is unmatched even in academic literature in the Chinese language.s
Introduction -- 1. Historical Perspectives on Chinese Written Language and Literacy Education in China -- 2. Literacy in Ancient China: A Culturally and Socially Situated Role in Historical Times -- 3. Foreign Literature Education in China$1 (Bs Secondary Schools from 1919 to 1949 -- 4. Influences of the Cultural Revolution on Chinese Literacy Instruction -- 5. Chinese Language Pedagogy and Human Dignity: The Special Rank Teacher in the Aftermath of the Cultural Revolution -- 6. Early Literacy Education in China: A Historical Overview -- 7. Chinese Youth Literature: A Historical Overview -- 8. Primary School Chinese Language and Literacy Curriculum Reforms in China After 1949 -- 9. High School Chinese Language and Literacy Curriculum Reforms -- 10. Chinese Lian Huan Hua and Literacy: Popular Culture Meets Youth Literature -- 11. Information and Communication Technologies for Literacy Education in China -- 12. Family Literacy in China.s
Keywords: Education; Applied linguistics; Language and languages; Literacy; Education; Language Education; Literacy; Applied Linguistics